Calcified fibrous pseudotumor with Castleman disease - Ismail Harmankaya; Nevzat Serdar Ugras; Tamer Sekmenli; Fatih Demir; Yavuz Köksal (University of São Paulo, 2018)
Simultaneous calcified fibrous pseudotumor (CFT) and Castleman disease (CD) is an extremely rare association. CD is an uncommon lymphoproliferative disease that can arise in various sites of the body, while CFT is a rare type of benign fibrous lesion that frequently affects children and young adults, occurring as solitary or multiple lesions throughout the human body. Both entities are rare and exhibit typical and diverse histomorphological features. We report the case of a 15-year-old female patient, who, at the age of 13 had a biopsy performed at an external medical center; however, after 4 months the lesion had regrown. This lesion was removed with a surgical operation; however, it regrew 2 years later and was removed a third time. The results of the latter two biopsies were the same: CFT accompanying CD. The histologic examination of the excised lymph node and the surrounding tissue showed hyalinized fibrous tissue containing dystrophic and psammomatous calcification. In this case, the hyaline vascular type of CD was found to be intertwined with a CFT, which hampered the differentiation of whether both entities emerged within the lymph node or if the CFT developed from the soft tissue and then involved the lymph node. Future studies involving larger case series will provide a more precise insight, which should serve to resolve the current uncertainty